Answer:
31.75 m/s
Step-by-step explanation:
h = 41.7 m
Let the initial velocity of the second stone is u
Let the time taken to reach to the bottom by the first stone is t then the time taken by the second stone to reach the ground is t - 1.8.
For first stone:
Use second equation of motion
![h=ut+(1)/(2)gt^2](https://img.qammunity.org/2020/formulas/physics/middle-school/h1m2payk8klxa7q51h382nn7h91ufz63ar.png)
Here, u = 0, g = 9.8 m/s^2 and t be the time and h = 41.7
So, 41.7= 0 + 0.5 x 9.8 x t^2
41.7 = 4.9 t^2
t = 2.92 s ..... (1)
For second stone:
Use second equation of motion
![h=ut+(1)/(2)gt^2](https://img.qammunity.org/2020/formulas/physics/middle-school/h1m2payk8klxa7q51h382nn7h91ufz63ar.png)
Here, g = 9.8 m/s^2 and time taken is t - 1.8 = 2.92 - 1.8 = 1.12 s, h = 41.7 m and u be the initial velocity
.... (2)
By equation the equation (1) and (2), we get
![41.7=1.12 u +4.9 * 1.12^(2)](https://img.qammunity.org/2020/formulas/physics/college/kj2rextq0m5m5d591o6rcm4aopxy0czj70.png)
u = 31.75 m/s